Integrate 2x/(x^2+3) using the substitution u=x^2+3

u=x2 + 3

du/dx=2x

dx=du/2x

2x/(x2+3) dx becomes (2x/u) * (du/2x)

the 2x terms cancel out giving 1/u du

this integrates to ln(u)+c becoming ln(x2+3)+c

Answered by Tom S. Maths tutor

12542 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

One important question type to be able to answer is integrating squared trig functions. like cos^2(x)


Differentiate y=ln(ln(x)) with respect to x.


How do I find the minimum or maximum of a quadratic function?


The curve C has equation: 2(x^2)y + 2x + 4y – cos(pi*y) = 17. Use implicit differentiation to find dy/dx in terms of x and y.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences